Respon Peternak terhadap Pencegahan dan Pengobatan Penyakit Cacing Gastrointestinal Pada Kambing di Desa Klopo Kecamatan Tegalrejo Kabupaten Magelang: Farmers Response on Prevention and Treatment Gastrointestine Worm Disease in Goat in Klopo Village Tegalrejo District Magelang Sub-Province - Budi Purwo Widiarso; Wida Wahidah Mubarokah (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2019)
This study was conducted to determine the response of farmers to the prevention and treatment gastrointestine worm disease in goats and know factors that influencing farmer response Tools and materials used are stationery, questioner, folder, worm drug and vitamin of B complex. The respondents were 30 people. Data was taken from pre-test and post-test by conducting direct interview regarding prevention and treatment gastrointestine worm disease in goat by using questioner. Based on the regression analysis obtained by multiple linear equations as follows: Y = 28.946 + 5.084X1 - 0,215X2 + 0,171X3+ 0,548X4 + e. From model of regresion above, it can be intepreted that each increase in the vallue of X1 (education) equal to 1 % will add respon equal to 5.084, each increase in the value of X2 (age) by 1 % will reduce the respon by 0.215, each increase of value of X3 (experience of farming) by 1 % will add value of respon equal to 0.171, and each increase of value of X4 (amount of the ownership of livestock) by 1 % will add value of 0.548. This study concluded that there was an increase in knowledge aspects of 14.87 with EP 82.6% and EPP 77.36%, attitude aspects amounting to 10.47 with EP 90.88% and EPP 82.12% and skills aspects of 5.1 with EP 86.6% and EPP 79.19% and an increase in response value from aspects of knowledge, attitudes, and skills of 30.39%, namely from a low response to a high response to the prevention and treatment of gastrointestinal worm disease in goats. Education is the most significant factor that has a very significant effect of (P 1 â‰¤0.01) on the farmer response average. Keywords: prevention, treatment, gastrointestine worm, goat, response